Dulce interior (2016)
"Dulce interior is a project that merges two universes: Woman's lingerie and Colombian typical confectionery from Bojacá. An underwear collection that narrates the most relevant aspects about the native patrimony residing inside these sweets. ... BRIEF Designing a women?s lingerie collection, which narrates the story and trends derivative from the Colombian typical confectionery of Bojacá, in order to generate a contact bridge where people from Bogota can meet part of their local unknown patrimony. This collection is inspired in 25 to 32 year-old women, who have enough economical income to seek for independency and explore into the redefinition of their own identity and style." -- Tomado del Formato de Documento de Grado.